Vulnerability Assessment of Fishing Communities in Kerala, Towards the Impact of Climate Change-With Special Reference to Cherai - Sarada Devi; Arunachalam P; Sachin Pavitran A.P (Faculty of Economics, Universitas Sriwijaya, 2018)
The fisheries sector in India and Kerala, though performing well, faces serious challenges such as socio-economic conflicts, low income to the common fishermen, low catch per unit effort, over exploitation of marine resources, unsustainable harvesting and also susceptibility to hazards related to climate change. These affect the production and progress of fisheries sector, which depends on the marine resources. The ill effects of climate change can take many forms including natural hazards, and can affect the livelihood of the farmers economically, socially, environmentally, and even physically. This can be addressed through regulation to over exploitation, diverting the fishermen to other livelihood sectors and by means of active participation of all the stakeholders in increasing the adaptive capacity through sustainable and planned capacity building strategies and development measures. This study deals with the socio economic characteristics of fishermen in Kerala and specifically studies the vulnerability assessment of fishing communities towards the impacts of climate change.